(untitled) (Annals of African Medical Research, 2019)
Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are blood borne viral infection with huge disease burden on pregnant women and their babies especially in Bauchi, Nigeria. Data on the prevalence rates of these infections would aid the clinical management and public health control of these infections. The study determined the prevalent rates of HIV, HBV and HCV among ante-natal care (ANC) attendees in health facilities in Bauchi State, north-eastern Nigeria. This is a a descriptive study that reviewed data secondarily from 13 health facilities in Bauchi State, Nigeria. Data were collected for a 12-month period from July 2017 - June 2018. The study found the following average prevalence rates among the ANC attendees: HIV (0.71%), HBV (1.57%) and HCV (0.64%). The study found low but significant prevalent rates of HIV, HBV and HCV infections among the ANC attendees. The study recommends for strengthening of preventive and curatives measures against these viruses among the pregnant women. These include health education, HBV vaccination, anti-retroviral therapy and early diagnosis and treatment of these viruses. The study also recommends for appropriate, complete and consistent medical records to monitor these viruses. Further studies are required for the HIV, HBV and HCV infections and their co-infections among the pregnant women.